Предмет: Математика,
автор: romaroman1
решить уравнение: (х-3)/5=(2х+3)/3
Ответы
Автор ответа:
0
5*(2x+3)=3*(x-3)
10x+15=3x-9
10x-3x=-9-15
7x=-24
x=-24:7
x=-3 3/7
10x+15=3x-9
10x-3x=-9-15
7x=-24
x=-24:7
x=-3 3/7
Автор ответа:
0
(х-3)/5=(2х+3)/3
3х-9=10х+15
3х-10х=15+9
-7х=24
х=-3 3/7
Ответ: -3 3/7
3х-9=10х+15
3х-10х=15+9
-7х=24
х=-3 3/7
Ответ: -3 3/7
Похожие вопросы
Предмет: Русский язык,
автор: AnsarAbu123456789
Предмет: Физика,
автор: nell1760
Предмет: География,
автор: Аноним
Предмет: Физика,
автор: yrzfadin
Предмет: Алгебра,
автор: Аноним